Effect of Temperature and Extraction Time on the Yield, Water Content, and Methoxyl of Coconut Fiber Pectin - Paat, Frangky J.; Lamaega, Jolanda Ch. E.; Mamuaja, Christine Fransin; Lumuindong, Frans; Rorong, Frangky (Journal of Agriculture, 2023)
This research aims to see the effect of temperature and extraction time on water content, yield and methoxyl content of coconut fiber pectin. This research was carried out experimentally factoril in Design Random Complete, which consists two treatment that is temperature extraction and extraction time with three repetitions. The results of this research show that treatment temperature extraction very influence yield pectin, rate water and methoxyl pectin while the extraction time affects the water content of the pectin. At a temperature of 70 O C and long extraction 60 minutes obtained the highest average yield of pectin, namely 4.31%, while the average the lowest pectin yield was obtained from treatment with an extraction temperature of 90 ° C and an extraction time of 90 minute. Average rate methoxyl highest obtained from treatment temperature 70 O C and long extraction 30 minute, whereas average percent rate methoxyl Lowest obtained from treatment with an extraction temperature of 90 O C and an extraction time of 90 minutes, namely 8.03% and 7.61% respectively. From the results obtained, it was concluded that the pectin obtained was classified as deep pectin group with high methoxyl content, namely >7%. Average percent of pectin content The lowest was 90 O C and the extraction time was 90 minutes, namely 10.19%, while the highest obtained from treatment with an extraction temperature of 70 O C and an extraction time of 30 minutes. From the results of the analysis this water content means that the water content of the coconut fiber pectin obtained is deep study this has fulfil condition for water content dry pectin that is 10-14%.